Public preferences regarding the priority setting criteria of health interventions for budget allocation: results of a survey of Iranian adults - Ali Darvishi; Rajabali Daroudi; Mehdi Yaseri; Ali Akbari Sari (BMC, 2022)
Abstract Objectives Priority setting in health directly impacts the general public as payers and final consumers, so the public preferences must be considered. The present study aimed to provide public preferences about health intervention allocation criteria for the optimal allocation of public health budget in Iran. Methods A choice-based survey method was used to assess the general public's preferences regarding 8 critical criteria with a societal aspect. One thousand sixty-four adult citizens of Tehran, Iran, participated in the study. Participants were asked to allocate a hypothetical budget between the two groups with differences in allocation criteria. Public preferences were inferred from absolute majority responses i.e., more than 50% of participants' allocation for a criterion. The Logistic Regression Model was used to investigate the factors affecting the preferences regarding the importance of allocation criteria. Results Based on expressed participants' preferences, criteria of disease severity, age, daily care needs, Number of alternative interventions, individual's economic status, and diseases with absence from work were important. Thus, 77, 69, 61, 57, 54, and 51% of participants preferred to allocate the hypothetical budget to the treatment of patients with poor economic status, treatment of patients with diseases leading to absence from work, treating patients with severe diseases, treatment of diseases in need of daily care and treatment of children's diseases, respectively. Findings from the factors affecting participants' preferences regarding allocation criteria also showed that people with different characteristics had different preferences. Conclusions Iranian general public pays special attention to the criteria of equitable allocation, including patients' economic status, criteria with societal aspects such as absenteeism from work and the need for daily care, as well as criteria with medical aspects such as disease severity and access to alternative interventions which may sometimes be less considered in decision making.